Modelling and optimisation of water management in sloping coastal aquifers with seepage, extraction and recharge - Mondal, Raka; Benham, Graham; Mondal, Sourav; Christodoulides, Paul; Neokleous, Natasa; Kaouri, Katerina (My University, 2019)
We consider the management of sloping, long and thin, coastal aquifers. We first develop a simple mathematical model, based on Darcy flow for porous media, which gives the water table height, and the flow velocity as a function of the underground seepage rate, the recharge rates and the extraction rates, neglecting sea water intrusion. We then validate the model with recent data from the Germasogeia aquifer which caters for most of the water demand in the area of Limassol, Cyprus. The data is provided over a three-year period by the Cyprus Water Development Department (WDD), the governmental department managing the aquifer. Three different models of the recharge sources have been considered and it was found that Gaussian sources give the closest agreement with data. Furthermore, based on our model, we subsequently develop an optimised recharge strategy and identify the optimal recharge rates for a desired extracted water volume while the water table height is maintained at the acceptable level. We study several scenarios of practical interest and we find that we can achieve considerable water savings, compared to the current empirical strategy followed by WDD. Additionally, we model the transport of pollutants in the aquifer in the case of accidental leakage, using an advection-diffusion equation and the concentration is determined in the aquifer for an ongoing contamination and two pulsed contaminations (pulse duration 1 day and 30 days, respectively). We find that in the case of an undetected and unhindered contamination (worst case scenario) the aquifer would get polluted in about three years. Also, we find that double recharge rates flush the pollutant out of the aquifer faster. Finally, to incorporate the possibility of sea water intrusion, which can render aquifers unusable, we develop a new, transient two-dimensional model of groundwater flow based on the Darcy-Brinkman equations, and determine the position of the water table and the seawater-freshwater interface for conditions of drought, moderate rainfall and flooding. The validation of the new seawater intrusion modelling approach has been carried out via comparison with a widely-accepted code.
Keywords: Aquifer; Darcy flow; Darcy-Brinkman equations; Mathematical modelling; Sea-water intrusion; Water management